Vibration of laminated shells and plates - Qatu, Mohamad S. (Mohamad Subhi) (Elsevier, 2004)
Vibrations drive many engineering designs in todays engineering environment. There has been an enormous amount of research into this area of research over the last decade. This book documents some of the latest research in the field of vibration of composite shells and plates filling a much-needed gap in the market. Laminated composite shells have many engineering applications including aerospace, mechanical, marine and automotive engineering. This book makes an ideal reference for researchers and practicing engineers alike. *The first book of its kind * Documents 10 years of research in the field of composite shells. * Many Engineering applications.